Relationship of amyloid-β1–42 in blood and brain amyloid: Ginkgo Evaluation of Memory Study. Issue 1 (27th November 2019) - Lopez, Oscar L; Klunk, William E; Mathis, Chester A; Snitz, Beth E; Chang, Yuefang; Tracy, Russell P; Kuller, Lewis H
Abstract: A blood test that predicts the extent of amyloid plaques in the brain and risk of Alzheimer's disease would have important benefits for the early identification of higher risk of dementia and Alzheimer's disease and the evaluation of new preventative therapies. The goal of this study was to determine whether plasma levels of amyloid-β1–42, 1–40 and the amyloid-β1–42/1–40 ratio among participants in the Pittsburgh centre of the Ginkgo Evaluation of Memory Study were related to the extent of brain fibrillar amyloid plaques measured in 2009 using Pittsburgh compound-B PET imaging, hippocampal volume, cortical thickness in the temporal lobe and white matter lesions. There were 194 participants who had Pittsburgh compound-B measurements in 2009 with the mean age of 85 years; 96% were white and 60% men. Pittsburgh compound-B positivity was defined as a standardized uptake value ratio of ≥1.57. Amyloid-β in blood was measured using a sandwich enzyme-linked immunosorbent assay developed by Eli Lilly and modified at the University of Vermont. All participants were nondemented as of 2008 at the time of study close out. The study sample included 160 with blood samples drawn in 2000–02 and 133 from 2009 and also had brain amyloid measured in 2009. All blood samples were analysed at the same time in 2009. Plasma amyloid-β1–42 was inversely related to the percent Pittsburgh compound-B positive (standardized uptake value ratio ≥1.57), β −0.04, P = 0.005. Practically all participants who were apolipoprotein-E4 positive at older ages were also Pittsburgh compound-B positive for fibrillar amyloid. Among apolipoprotein-E4-negative participants, quartiles of amyloid-β1–42 were inversely related to Pittsburgh compound-B positivity. In multiple regression models, plasma amyloid-β1–42 measured in 2000–02 or 2009 were significantly and inversely related to Pittsburgh compound-B positivity as was the amyloid-β1–42/1–40 ratio. There was a 4-fold increase in the odds ratio for the presence of Pittsburgh compound-B positivity in the brain in 2009 for the first quartile of amyloid-β1–42 as compared with the fourth quartile in the multiple logistic model. This is one of the first longitudinal studies to evaluate the relationship between amyloid-β1–42 in the blood and the extent of brain amyloid deposition measured by PET imaging using Pittsburgh compound-B. Our findings showed that remote and recent low plasma amyloid-β1–42 levels were inversely associated with brain amyloid deposition in cognitively normal individuals. However, changes in plasma amyloid-β1–42 over time (8 years) were small and not related to the amount of Pittsburgh compound-B. Abstract : We have found an inverse relationship between plasma levels of amyloid-β1–42 in blood collected in 2000–02 ( n = 160) and for same individuals in 2009 ( n = 133) and amount of fibrillar amyloid measured by Pittsburgh compound-B in 2009. There was about a 4-fold higher risk of fibrillar amyloid for the first versus fourth quartile of amyloid-β1–42 in blood. Graphical Abstract: